Analisis Penentuan Harga Pokok Produksi dengan Metode Full Costing dan Variabel Costing Sebagai Dasar Penentuan Harga Jual pada Toko Imelda Bakery - Albertini Noveritas Putri Darabogar; Henrikus Herdi; Siktania Maria Diliana (Universitas 45 Surabaya, 2024)
This research aims to determine the determination of product selling prices using a full costing and variable costing approach at the Imelda bakery shop. The data sources used in this research are primary data and secondary data. Primary data in this research is from interviews, and secondary data in this research is from financial report data. Data collection techniques used in this research were observation, interviews and documentation. The data analysis technique used in this research, namely quantitative descriptive analysis, is used to explain calculations using the full costing method and variable costing in determining the cost of production and then this information will be used as a basis for determining product selling prices. The results of the research show that the calculations use the method full costing produces higher production value compared to using the variable costing method. This is because the full costing method includes all costs, both fixed and variable, in the calculation of the cost of production, whereas the variable costing method does not include all types of costs, only variable costs.